2019
DOI: 10.1021/acscatal.8b03734
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Carbon Lattice-Defect Regulating Electrochemical Oxygen Reduction to Hydrogen Peroxide Production over Nitrogen-Doped Graphene

Abstract: Carbon-based materials are considered to be active for electrochemical oxygen reduction reaction (ORR) to hydrogen peroxide (H2O2) production. Nevertheless, less attention is paid to the investigation of the influence of in-plane carbon lattice defect on the catalytic activity and selectivity toward ORR. In the present work, graphene precursors were prepared from oxo-functionalized graphene (oxo-G) and graphene oxide (GO) with H2O2 hydrothermal treatment, respectively. Statistical Raman spectroscopy (SRS) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(178 citation statements)
references
References 62 publications
6
165
0
7
Order By: Relevance
“…The catalyst exhibited 454, 378, and 302 mmol g −1 cat h −1 average H 2 O 2 production rates under potentials of 0.1, 0.3, and 0.5 V versus RHE, respectively. Among previously reported noble‐metal‐based [ 13,14,43 ] and carbon‐based [ 21,22,25 ] electrocatalysts, {001}‐Fe 2 O 3– x achieved the highest H 2 O 2 production rate. The room‐temperature H 2 O 2 decomposition test confirmed that {001}‐Fe 2 O 3– x is inactive in the decomposition of H 2 O 2 (Figure S33, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst exhibited 454, 378, and 302 mmol g −1 cat h −1 average H 2 O 2 production rates under potentials of 0.1, 0.3, and 0.5 V versus RHE, respectively. Among previously reported noble‐metal‐based [ 13,14,43 ] and carbon‐based [ 21,22,25 ] electrocatalysts, {001}‐Fe 2 O 3– x achieved the highest H 2 O 2 production rate. The room‐temperature H 2 O 2 decomposition test confirmed that {001}‐Fe 2 O 3– x is inactive in the decomposition of H 2 O 2 (Figure S33, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…100 Nevertheless, most of the reported nitrogen-doped carbon materials led to the four-electron ORR to H 2 O, and only a few samples were reported to exhibit high selectivity toward H 2 O 2 production. 63,97,[101][102][103][104] For example, Anderson's group investigated the ORR performance of nitrogen-doped Ketjenblack for H 2 O 2 production from both experimental and theoretical calculation viewpoints. 105 Experimental results demonstrated that the nitrogen-doped Ketjenblack showed a lower onset potential and mainly followed the two-electron ORR process for H 2 O 2 production.…”
Section: Metal-free Carbon-based Materialsmentioning
confidence: 99%
“…2f). The important role of defects for two-electron ORR was also investigated and demonstrated in other carbon materials [26][27][28][29].…”
Section: Sp 2 -C Defectsmentioning
confidence: 99%